Explanation for twin tunnelling-induced surface settlements by changes in soil stiffness on account of stress history. (March 2019) - Zhang, Tianqi; Taylor, R. Neil; Divall, Sam; Zheng, Gang; Sun, Jibin; Stallebrass, Sarah Elizabeth; Goodey, Richard James
Abstract: In this article, a group of representative centrifuge tests were selected for numerical modelling to explain the surface settlements induced by sequential twin tunnelling. Both Modified Cam Clay model (MCC) and Three-Surface Kinematic Hardening model (3-SKH) were adopted in the simulation, which indicated the use of 3-SKH model conduced to mimicking more closely centrifuge model response. Via performing more contrastive numerical analyses with 3-SKH model, the influence of the first tunnel event on the stiffness of the soil around the second tunnel was quantitatively investigated, whereby the mechanism behind the observed surface settlements was finally made clear.